Nucleotide‐Binding Oligomerization Domain (NOD)-Like Receptor Subfamily C (NLRC) as a Prognostic Biomarker for Glioblastoma Multiforme Linked to Tumor Microenvironment: A Bioinformatics, Immunohistochemistry, and Machine Learning-Based Study - Han S; Zhang Z; Ma W; Gao J; Li Y (Dove Medical Press, 2023)
Shiyuan Han,1 Zimu Zhang,2 Wenbin Ma,1 Jun Gao,1 Yongning Li1,3 1Department of Neurosurgery, Chinese Academy of Medical Sciences and Peking Union Medical College, Peking Union Medical College Hospital (Dongdan Campus), Beijing, People's Republic of China; 2Department of General Surgery, Chinese Academy of Medical Sciences and Peking Union Medical College, Peking Union Medical College Hospital (Dongdan Campus), Beijing, People's Republic of China; 3Department of International Medical Service, Chinese Academy of Medical Sciences and Peking Union Medical College, Peking Union Medical College Hospital (Dongdan campus), Beijing, People's Republic of ChinaCorrespondence: Yongning Li, Department of Neurosurgery and Department of International Medical Service, Chinese Academy of Medical Sciences and Peking Union Medical College, Peking Union Medical College Hospital (Dongdan campus), No. 1 Shuaifuyuan Wangfujing Dongcheng District, Beijing, People's Republic of China, Tel +86 13901074129, Fax +86 1069152530, Email 13901074129@139.comPurpose: Glioblastoma multiforme (GBM) remains the deadliest primary brain tumor. We aimed to illuminate the role of nucleotide‐binding oligomerization domain (NOD)-like receptor subfamily C (NLRC) in GBM.Patients and Methods: Based on public database data (mainly The Cancer Genome Atlas [TCGA]), we performed bioinformatics analysis to visually evaluate the role and mechanism of NLRCs in GBM. Then, we validated our findings in a glioma tissue microarray (TMA) by immunohistochemistry (IHC), and the prognostic value of NOD1 was assessed via random forest (RF) models.Results: In GBM tissues, the expression of NLRC members was significantly increased, which was related to the low survival rate of GBM. Additionally, Cox regression analysis revealed that the expression of NOD1 (among NLRCs) served as an independent prognostic marker. A nomogram based on multivariate analysis proved the effective predictive performance of NOD1 in GBM. Enrichment analysis showed that high expression of NOD1 could regulate extracellular structure, cell adhesion, and immune response to promote tumor progression. Then, immune infiltration analysis showed that NOD1 overexpression correlated with an enhanced immune response. Then, in a glioma TMA, the results of IHC revealed that the increase in NOD1 expression indicated high recurrence and poor prognosis of human glioma. Furthermore, the expression level of NOD1 showed good prognostic value in the TMA cohort via RF.Conclusion: The value of NOD1 as a biomarker for GBM was demonstrated. The possible mechanisms may lie in the regulatory role of NLRC-related pathways in the tumor microenvironment.Keywords: glioblastoma multiforme, NLRC family, biomarker, tumor microenvironment, prognostic model, tissue microarray